Teaching/Writing in Thirdspaces : The Studio Approach - Grego, Rhonda C. (Book collections on Project MUSE., 2007)
Teaching/Writing in Thirdspaces: The Studio Approach examines a dynamic approach to teaching composition that reimagines not only the physical space in which writing and learning occurs but also the place occupied by composition in the power structure of universities and colleges. In response to financial and programmatic cutbacks at the University of South Carolina in the 1990s, authors Rhonda C. Grego and Nancy S. Thompson used their academic backgrounds in composition and English education, along with their personal histories in working-class families, to look at compositional spaces and.